Reactive Oxygen Intermediate (ROI) in Dog Macrophage Infected with Mycobacterium tuberculosis - Ida Tjahajati (Universitas Gadjah Mada, 2006)
experiment used 24 healthy dogs, aged between 1 and 2 years, both male and female which were divided into twodifferent groups consisting of 12 dogs each. The first group was the treatment group, that is they were infected with Mtuberculosis and the second one was the control group. The activity of macrophages ROI secretion were measured at1st, 2nd, 12th, and 24th after infection using nitroblue tetrazolium (NBT) reduction assay. Three cats were used to measure themacrophage activity in each period, using triplicate sample for each cat. The results of the experiment showed thatROI secretion increased in infected group compared with the control group, and this activity reached to the plateaulevel at 2 weeks after infection. Although these enhanced activities were gradually diminished thereafter, higherlevels of these activities were consistently observed until the end of experiment compared with control group. Theresults of the experiment indicated that ROI played an important role to against M.tuberculosis infection in dogs.Keyword: macrophage, ROI, M.tuberculosis, dogs